Stoichiometry and volume dependent transport in lithium ion memristive devices - Charis M. Orfanidou; Panagiotis S. Ioannou; Evripides Kyriakides; Christiana Nicolaou; Cristian N. Mihailescu; Van Son Nguyen; Van Huy Mai; Olivier Schneegans; John Giapintzakis (AIP Advances, 2018)
LixCoO2, a thoroughly studied cathode material used extensively in Li-ion rechargeable batteries, has recently been proposed as a potential candidate for resistive random access memory and neuromorphic system applications. Memristive cells based on LixCoO2 thin films have been grown on Si substrates and two-probe current-voltage measurements were employed to investigate the origin and nature of resistive switching behavior exhibited by these cells. The results indicate that a voltage-driven metal-to-insulator transition of the active LixCoO2 layer is responsible for the resistive switching behavior, which has a homogeneous nature.